Subordinated clauses usage and assessment of syntactic maturity: A comparison of oral and written retellings in beginning writers - Silva, María Luisa (2010)
The present longitudinal study aims to explore possible syntactic complexity differences between oral and written story retellings produced by Spanish speaking children at the end of the 1st and 2nd grades of primary education. It is assumed that differences between oral and written modalities can be found due in part to the cognitive demands of low level writing skills. Indeed, it has been observed that written texts produced by children are shorter and of lower quality than oral ones (Berninger, et al., 1992; Berninger & Swanson,1994). However, how the transcription skills might constrain the syntactic complexity of children's written texts is not well established. The children (N=163) that participated in this study were attending three different schools located in Córdoba Province, Argentina. The children were examined at the end of the 1st and 2nd year of primary education. The oral and written retellings were analyzed using Length, T- unit number and Syntactic Complexity Index (SCI) (Hunt, 1965; 1970). The analysis o ff children's productions showed differences between grades and modalities. The differences between modalities were found in text Length and T-unit, but not in SCI. These results suggest that transcription skills do not affect syntactic performance. Nevertheless, a more detailed analysis revealed differences between groups. Possible restrictions of the original text on children's performance were also observed. The implications and the scope of the SCI and units used for the analysis are furthered discussed.